2017
DOI: 10.1332/175982717x14940647262909
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of activation policy targeting young adults with health-related problems in Sweden and Denmark

Abstract: The Scandinavian countries have a long history of active labour market policy, using activation to promote work among those with no problems besides unemployment. However, activation policy is now permeating social policies providing economic protection for young adults who cannot work for health reasons, which has been legitimised through a strong emphasis on paid work as the main source of social participation. In this article, we discuss the consequences of this activation policy in Denmark and Sweden, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…From the clients' perspective, an overly narrow focus on employability seems to negatively impact service users' feelings of dignity (Ohls, 2020). Hultqvist and Nørup (2015, 2017) showed that activation policies that only focus on work have negative consequences for people with health problems and can increase stigmatisation and exclusion. Previous studies on the effectiveness of ALMPs indicate that certain ALMPs work better for specific target groups.…”
Section: Social Work and The Activation Of Disadvantaged Target Groupsmentioning
confidence: 99%
“…From the clients' perspective, an overly narrow focus on employability seems to negatively impact service users' feelings of dignity (Ohls, 2020). Hultqvist and Nørup (2015, 2017) showed that activation policies that only focus on work have negative consequences for people with health problems and can increase stigmatisation and exclusion. Previous studies on the effectiveness of ALMPs indicate that certain ALMPs work better for specific target groups.…”
Section: Social Work and The Activation Of Disadvantaged Target Groupsmentioning
confidence: 99%
“…In the 1980s and 1990s activation was targeted at those citizens with no serious problems besides unemployment. Since then the ideas of activation have extended to the sphere of social and welfare policies and practices (Karjalainen & Saikku, 2011;Heidenreich & Graziano, 2014, p. 1;Hultqvist & Nørup, 2017). For that reason employment, social and welfare policies have increasingly been intertwined and focused on activating various social groups such as the long-term unemployed, women, younger and older people, migrants, young mothers, the unskilled and the disabled (Heidenreich & Graziano, 2014;Lantz & Marston 2012).…”
Section: Extending Sphere Of Activation and Responsibilisationmentioning
confidence: 99%
“…Hence, labour-market exclusion is identified as a crucial pathway when individuals with chronic illnesses become marginalized. At the policy level, labour-market inclusion is therefore often viewed as the success criterion for societal inclusion as well as the solution to various social and (mental) health problems (Hultqvist and Nørup, 2017; Nørup, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Yet the evidence supporting the theoretical assumption for individuals with chronic illnesses and in the context of advanced welfare is very limited. This is also the case in examining the evidence for the effectiveness of activation policies targeting persons with pre-existing chronic illnesses (Hultqvist and Nørup, 2017).…”
Section: Introductionmentioning
confidence: 99%